“TIRINNANZI” OR “TYRYNNANZY”? THE GIORNALINO DI GIAN BURRASCA AND LUIGI BERTELLI’S MORDANT IRONY ON NAMES - Geddes da Filicaia, Costanza (PALIMPSEST / ПАЛИМПСЕСТ, 2016)
This essay analyses the names chosen by Vamba (Luigi Bertelli) for the characters of his very famous novel Il giornalino di Gian Burrasca (1907-1908). The introduction gives an account of the plot and of the main characteristics of the novel, which is set in Florence in early twentieth century. It focuses on the fact that Giannnino, the main character, is an unloved child and that the adults who surround him are extremely strict, narrow-minded and hypocritical. It then gives and account of the names chosen by Vamba (it is, as far as we could verify, the first essay on this topic). The conclusions are: 1. Nicknames are used for children mainly because, besides being small, in that society they didn’t have a strong social identity. 2 In this novel names often have a hypocoristic meaning. 3 The early Twentieth century the Italian society, in which the novel is set, appreciated foreign spelling of the names, while later Fascism will forbid it 4. The choice of nicknames and peculiar names is typical of Tuscan and Florentine tradition. At the end, the essay states that Vamba made a very careful selection of the characters’ names and that these names are very meaningful.Keywords: Childhood, Hypocoristic purpose, Nicknames, Onomastics, Xenophilia.